Mature age women aged care workers: Summary of survey data (Wave1) - Austen, Siobhan; Jefferson, Therese; Lewin, Gill; Sharp, R. (2013)
The Mature Age Women in Aged Care (MAWAC) survey was conducted nationally in two waves from 2011 to 2013 as part of an ARC Discovery Grant Project (DP110102728): Missing Workers: Retaining Mature Age Women Workers to Ensure Future Labour Security. The project was conducted by researchers at Curtin University in Perth and the University of South Australia in Adelaide. The two waves of data collection were designed to address the need for longitudinal data to analyse the workforce decision-making of mature age women. The survey focused on the aged care sector as it represents an important sector for mature age women. The purpose of this paper is to summarise the data that was collected from the first wave of the MAWAC survey, with the aim of providing information on the characteristics and experiences of mature age women working in aged care. The tables in this paper reflect specific questions in the survey document and provide the frequency and distribution of responses to each question.